Excessive exposure to digital media: the formative years and children response to schooling environment - Urien, James; Enoja, Silas Courage; Odofin, Toyin; Obro, Sunday (Journal of Education and Learning (EduLearn), 2026)
This study investigated the correlation between excessive exposure to digital media in the formative years and how children respond to the schooling environment in Nigeria. This study employed the correlational research design. The study sample involved 150 primary school pupils. The instrument for the study “digital media usage, types of digital media, and response” was used for data collection. The research questions were answered with Pearson product moment correlation, while hypotheses were tested with linear regression. The study revealed a statistically significant negative correlation between digital media use and how children respond to the schooling environment in Nigeria, as well as a positive relationship between the type of digital media use and how children respond to the schooling environment in Nigeria. Founded on the findings, the study recommended that parents should encourage a healthy mix of activities. Limit screen time, designate media-free zones, and promote activities like reading, outdoor play, and face-to-face socializing; schools should integrate technology strategically to enhance classroom learning. Explore educational apps, games, and online resources suitable to different learning styles. The government should consider developing age-appropriate guidelines for healthy digital media utilization in partnership with educators, parents, and health professionals.